2014
DOI: 10.1002/chem.201304181
|View full text |Cite
|
Sign up to set email alerts
|

Design of Ratiometric Fluorescent Probes Based on Arene–Metal‐Ion Interactions and Their Application to CdII and Hydrogen Sulfide Imaging in Living Cells

Abstract: Non-coordinative interactions between a metal ion and the aromatic ring of a fluorophore can act as a versatile sensing mechanism for the detection of metal ions with a large emission change of fluorophores. We report the design of fluorescent probes based on arene-metal-ion interactions and their biological applications. This study found that various probes having different fluorophores and metal binding units displayed significant emission redshift upon complexation with metal ions, such as Ag(I), Cd(II), Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Due to its simplicity and rapidity, TDDFT is currently the most convenient and popular method for calculating VTEs. It can provide direct excited‐state information and show good agreement with experimental spectral results for fluorescent probes, as exemplified in several previous studies . VTE calculation can allow attribution of UV/Vis and fluorescence bands based on the S 0 and S 1 geometries, respectively, and then get contributions of FMOs.…”
Section: Methodssupporting
confidence: 66%
“…Due to its simplicity and rapidity, TDDFT is currently the most convenient and popular method for calculating VTEs. It can provide direct excited‐state information and show good agreement with experimental spectral results for fluorescent probes, as exemplified in several previous studies . VTE calculation can allow attribution of UV/Vis and fluorescence bands based on the S 0 and S 1 geometries, respectively, and then get contributions of FMOs.…”
Section: Methodssupporting
confidence: 66%
“…These results demonstrated that AM-contact sensing works in living cells to enable ratio imaging of the metal ions. Our previous results 17,22 and reports by Czarnik 27 and Hancock 20,28,29 suggested that the contactinduced emission shift was limited to rather large 4d-and 5d-block metal ions such as Cd(II) and Ag(I). In this paper, we demonstrated for the first time that AM-contact sensing could also work with the smaller 3d-block metal ions such as Zn(II) and Cu(II).…”
Section: Ratio Imaging Of Metal Ions In Live Cellsmentioning
confidence: 65%
“…A set of the AMcontact probes provided a multicolor fluorescence sensing system, which enabled us to distinguish several metal ions by one-pot single titration and principal component analysis (PCA) We previously reported that a Type-I probe serves as the ratiometric fluorescent chemosensor for metal ions based on AM-contact sensing (Figure 1). 17 For example, probe 1, bearing two sets of 2,2′-dipicolylamine (i.e., R = 2-pyridyl), exhibited a large emission red-shift upon binding with Cd(II), which was induced by forming van der Waals contact between the C9 carbon of the fluorophore and the metal ion in a 1:1 binding complex. However, while Type-I probes fluorescently responded to 4d-and 5d-block metal ions such as Cd(II), Ag(I), and Hg(II), they did not show an emission shift with 3d-block metal ions such as Zn(II).…”
mentioning
confidence: 99%
“…2, the fluorescence chemosensor FP displayed strong green fluorescence at 515 nm in HEPES aqueous buffer with pH 7.4. By the addition of 3×10 -4 M of Fe 3+ , the fluorescence intensity of FP (10 µM) was completely quenched (the quenching efficiency at 515 nm was 94%), which could be 80 ascribed to the paramagnetic quenching effect of Fe 3+ and/or ligand to metal charge transfer (LMCT). 13 Job's plot analysis confirmed that FP-Fe 3+ ensemble was formed according to a 1:1 stoichiometry (Fig.…”
Section: Fluorescence Emission Spectrum Studies Of Fp With Various Mementioning
confidence: 99%